La hegemonía en Gramsci y la reproducción de una visión del mundo - Mauricio Puentes Cala (Cambios y Permanencias, 2015)
This short papertriesto approachthe concept of hegemonyin Antonio Gramsci, through the study of a littlefragment of his vast and formlessdiscursive work, in order to identify the meaning of concurrent articulated intentions in ideological-cultural transmission and addressing moral and intellectual processes, pedagogical dimensions that contribute to the achievement of a historical unity.